Innovative experimental reduced scale model of road tunnel equipped with realistic longitudinal ventilation system. (February 2016) - Cascetta, Furio; Musto, Marilena; Rotondo, Giuseppe
Highlights: Innovative reduced scale model road tunnel. Authors have made and characterized experimentally a reduced scale impulsive jet fan. Tunnel subsection equipped with a realistic ventilation system. Abstract: Road tunnels require ventilation system for different reasons in order to provide a good level of safety and effectiveness in ordinary service and, in case of fire, to prevent the upstream smoke flow (back-layering phenomena). To evaluate the ventilation system, full scale experiments are more expensive both in terms of the costs and time, and the CFD model has high uncertainty without experimental validation. In this paper the authors have made and characterized experimentally a reduced scale impulsive jet fan in order to carry out a scaled longitudinal road tunnel subsection equipped with a realistic ventilation system. This innovative reduced scale model of road tunnel could give more relevant information such as phenomenology and performance of full-scale tunnel using suitable similarity rules. It could be useful to do parametrical studies or to focus on particular physical aspects (i.e. smoke pattern of thermal plume behavior with respect to usual experimental sections reported in literature). The innovative reduced scale model presented in this paper can provide a useful alternative method with respect to the full-scale experiments. Moreover, the authors have simulated numerically, by means the CFD commercial software FLUENT®, the scaled road tunnel and have compared experimental and numerical results in terms of axial velocity.